Between the Global, the National and the Local in Japan: Two Musical Pioneers from Sendai. Issue 2 (31st July 2017) - Mehl, Margaret
Abstract : Western visitors to Japan are often surprised at how widely European art music can be heard. The roots of what is arguably one of Japan's greatest success stories lie in the systematic introduction and dissemination of Western music by the government after the Meiji Restoration of 1868. Much research has focused on the government's role; but how was Western music disseminated and received in different parts of Japan? This article discusses the roles of two brothers, Shikama Totsuji (1853–1928) and Shikama Jinji (1863–1941), who in different ways contributed significantly to the dissemination of Western music beyond Tokyo and in particular to the northern provincial town of Sendai.